Field-Induced Dysprosium Single-Molecule Magnet Based on a Redox-Active Fused 1,10-Phenanthroline-Tetrathiafulvalene-1,10-Phenanthroline Bridging Triad - Lefeuvre, Bertrand; Galangau, Olivier; Gonzalez, Jessica Flores; Montigaud, Vincent; Dorcet, Vincent; Ouahab, Lahcène; Le Guennic, Boris; Cador, Olivier; Pointillart, Fabrice (Frontiers in Chemistry, 2018)
Tetrathiafulvalene and 1,10-phenanthroline moieties present respectively remarkable redox-active and complexation activities. In this work, we investigated the coordination reaction between the bis(1,10-phenanthro[5,6-b])tetrathiafulvalene triad (L) and the Dy(hfac)32H2O Metallo precursor. The resulting [Dy2(hfac)6(L)]CH2Cl2C6H143 (1) dinuclear complex showed a crystal structure in which the triad L bridged two terminal Dy(hfac)3 units and the supramolecular co-planar arrangement of the triads is driven by donor-acceptor interactions. The frequency dependence of the out-of-phase component of the magnetic susceptibility highlights three distinct maxima under a 2000 Oe static applied magnetic field, a sign that 1 displays a Single-Molecule Magnet (SMM) behavior with multiple magnetic relaxations. Ab initio calculations rationalized the Ising character of the magnetic anisotropy of the DyIII ions and showed that the main anisotropy axes are perpendicular to the co-planar arrangement of the triads. Single-crystal rotating magnetometry confirms the orientation of the main magnetic axis. Finally combining structural analysis and probability of magnetic relaxation pathways through Quantum Tunneling of the Magnetization (QTM) versus excited states (Orbach), each DyIII center has been attributed to one of the three observed magnetic relaxation times. Such coordination compound can be considered as an ideal candidate to perform redox-magnetic switching.